Investigation on Solar-Powered Electrocoagulation (SPEC) for the Treatment of Domestic Wastewater (DWW) - Senthil Kumar Muniasamy; Tariku Tadesse Gameda; Lenin Sundar Mallaian; Ilango Rengaraju; Jeyasudha Segaran; Yuvarani Periyasamy; Palpandian Murugesan; Suthagar Subramanian (Advances in Materials Science and Engineering)
Solar-powered electrocoagulation (SPEC) was used for the treatment of domestic wastewater by using aluminum electrodes. As a single-unit process for treating household wastewater, the EC is solar-powered. The aim of this research was the removal of chemical oxygen demand (COD), TDS, and turbidity by SPEC. Optimization of various operating parameters such as pH, voltage/current, electrode gap, and pollutant concentration was first performed using direct electrical current. By using batteries and charge controllers with panels, the SPEC reactor has achieved consistent and efficient performance. The effects of COD, turbidity, and TDS exclusion of functioning parameters such as density (8–40 A/m2) and detention time (5–30 min) were examined. The COD reduction was 85%, and removal efficiency of TDS and turbidity was 70.18% and 87.4%. The results have shown the technical feasibility of SPEC design as a potential method for domestic wastewater treatment by electrocoagulation. Further analytical study of sludge was also performed by FTIR and XRD analysis.